The Evaluation of WWTP with Activated Sludge Technology Combined with Microorganism Biofilters in IMERI Building - Khalida Hanum (Applied Research on Civil Engineering and Environment (ARCEE), 2021)
The regulations said that all domestic wastewater first should be treated before being discharged into public drainages. Therefore, IMERI building, as a research and education building located in the Faculty of Medicine, Universitas Indonesia, applies a wastewater management system using activated sludge technology combined with microorganism biofilters. This system is expected to treat the waste generated inside the building. It reprocesses become recycled water and partially discharged into city drainages based on the quality standard and maintenance applied during the operation. By collecting and evaluating primary and secondary data from system planning and routine maintenance results, we assess all performance of the WWTP system. Moreover, this system runs well and has all indicators of effluent categorizes safe. However, routine maintenance and the treatment process with chlorination and tighter monitoring should be taken seriously to keep the whole system's performance.